2021
DOI: 10.2147/ijgm.s335400
|View full text |Cite
|
Sign up to set email alerts
|

New Thresholds for AFP and Des-γ-Carboxy Prothrombin in Chronic Liver Disease Depending on the Use of Nucleoside Analogs and an Integrated Nomogram

Abstract: Background The thresholds of alpha-fetoprotein (AFP) and des-gamma-carboxy prothrombin (PIVKA-II) when detecting hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) patients with antiviral nucleoside analog (NA) remain controversial. A relevant integrated nomogram needs to be developed. Methods We enrolled a consecutive series of 5666 cases diagnosed with CHB either with or without antiviral agents and randomly allocated them to the training set (n=3966, 70.00%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Even though both AFP and PIVKA-II are useful diagnostic markers for HCC, a previous report found that they may not be a good marker for small HCC nodules less than 2 cm as they have sensitivity of approximately 50% (29). However, they may be used for HCC detection particularly in hepatitis virus-related HCC (22,30). A study from China found similar findings as this study but different cutoff for both AFP and PIVKA-II (31).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Even though both AFP and PIVKA-II are useful diagnostic markers for HCC, a previous report found that they may not be a good marker for small HCC nodules less than 2 cm as they have sensitivity of approximately 50% (29). However, they may be used for HCC detection particularly in hepatitis virus-related HCC (22,30). A study from China found similar findings as this study but different cutoff for both AFP and PIVKA-II (31).…”
Section: Discussionsupporting
confidence: 79%
“…These causes related to HCC deaths in 33%, 30%, and 21%, respectively (1). High-risk patients for HCC were patients with cirrhosis, chronic HBV diagnostic method particularly for HCC including AFP and PIVKA-II (20)(21)(22). The advantage of AFP is widely available, while PIVKA-II is highly specific to HCC.…”
Section: Introductionmentioning
confidence: 99%